Aplikasi Ergonomi Dengan Metode Rapid Entire Body Assesment (REBA) di Bagian Gudang Studi Kasus PT. XYZ - Priyanto, Fiki; Mellyka, Dhea; Tri Pambudi, Andika; Nurjaman, Dede; Catur Kurniawan, Rachman; Supriyanto, Supriyanto (JURNAL TEKNIK INDUSTRI, 2023)
PT. XYZ is a manufacturing company that manufactures auto parts. This research focuses on the warehouse section. During the activity, most of the operators complained of pain in some part of their body. These complaints will be identified using the Standard Nordic Questionnaire (SNQ). Then assess work posture using Rapid Whole Body Assessment (REBA). Actual working conditions will be obtained, analyzed and evaluated. The result of the preparation of finished goods is that the level of risk in the activity is moderate and requires improvement. When pulling/pushing goods to warehouse locations and to production buildings, loading onto trucks is a high-risk activity that requires immediate repair. The recommended suggestion is to reposition the operator's work position, add enough space to place the pallet so that the operator has more freedom. Apart from that, it is also necessary to add tools to place goods or parts on a higher platform, add equipment to protect the operator's back.